Evaluation of zone disinfection by air-passable plasma filter in a novel chamber model. (October 2022) - Baek, K.H.; Kim, S.-J.; Kim, T.; Hwang, Y.; Park, J.Y.; Yang, J.-Y.; Ryoo, S.; Lee, S.
Summary: Background: Disinfection of shared spaces has become essential to minimize the spread of various diseases. An efficient disinfection device that can simultaneously inactivate airborne bacteria and surface-adhered bacteria in an enclosed space is required. Aim: An air-passable plasma filter (APF) was developed and applied to a chamber model to evaluate the efficacy of zone disinfection. Methods: The 60 L chamber consisted of a nebulizer, circulation fans, temperature and humidity monitors, an air-sampling port with a sealed gate, airborne bacteria-trapping media, and a built-in fan for evaluation. After spraying each bacterial strain ( Escherichia coli, Staphylococcus epidermidis, and Mycobacterium smegmatis ) as a bioaerosol, airborne and surface-attached bacteria were quantified simultaneously to evaluate the zone-disinfection effect of APF. Findings: The operation of APF in the 60 L chamber showed a complete zone-disinfection effect for E. coli (10 min), S. epidermidis (10 min), and M. smegmatis (60 min) present in the air and on the walls at various locations. The time required to completely disinfect each of the airborne bacteria and surface-attached bacteria within the same space was different. Conclusion: APF has the potential to exhibit significant germicidal effects on various micro-organisms and can be an effective alternative for disinfection of enclosed spaces.